Respostas

2014-02-27T21:58:21-03:00
3.2 - 2b + c = 10                        3.1 - b + c= 3                         -2b + c = -2
12 - 2b + c = 10                         3 - b + c = 3                              b - c = 0
-2b + c = -2                                  -b + c = 0 (-1)                            -b = -2
                                                                                                    b= 2

                                                                                            2 - c = 0 
                                                                                                 c = 2